Pentingnya Filosofi dalam Pendidikan Menurut Perspektif Aksiologi dan Epistimologi Pendidikan Karakter Islami di Era Society 5.0 - Al Hadiq, Afifudin; Rahayu, Afinda; Sobirin, Ahmad Muhajir; Munawaroh, Nurul Latifah (Social Science Academic, 2023)
Philosophy is a science that investigates the causes and effects of everything. Modern philosophy is widely known as the philosophy of education. Educational philosophy has several streams, one of which is essentialism educational philosophy. Essentialism is a stream that is rooted in a basic learning subject. Epistemology is a branch of philosophy that examines knowledge that covers many areas of scope or scope that includes many sources, characters and human nature. Islamic character education is very important to be taught both in the family, community and in educational institutions, namely in schools. Current education should focus more on character education. So as to make the generation of good and globally competitive countries, especially in the 5.0 revolution era. This research method is basically a literature review method. This might happen because they lack education about ethics both at school and outside of school. Ethics education really needs to be done to overcome this problem. Ethics education is obviously very important in the current education system. The progress of education in one country, especially in Indonesia, can be seen from the successful implementation of character education for students. One of the possible changes in character through the provision of character education to them. The research method used is to conduct a literature review using relevant books or journal articles.